The Factor Structure of the Polish-Language Version of the Romantic Beliefs Scale - Katarzyna Adamczyk; Sandra Metts (Psychological Topics, 2014)
The aim of the present study was to investigate the factor structure and psychometric properties of the Polish adaptation of Romantic Beliefs Scale (RBS; Sprecher & Metts, 1989). In a sample of 414 Polish university students aged 19-25 (227 females and 187 males), the factor structure of the original English version was confirmed for the four subscales: Love Finds a Way, One and Only, Idealization, and Love at First Sight. The present study provides evidence that the 15-item version of the Polish adaptation of the (RBS) possesses a factor structure and psychometric properties comparable to the English-language version of RBS. It was shown to be a reliable self-report measure for romantic beliefs within a sample of the Polish population. The development of a new Polish measure of romantic beliefs has provided further validation for the RBS, and provided evidence in support of the ideology of romanticism in various populations, and indicated the importance of differentiating between the different types of romantic beliefs.